Integrated systems biology approach identifies gene targets for endothelial dysfunction - Pinheiro-de-Sousa, Iguaracy; Fonseca-Alaniz, Miriam Helena; Giudice, Girolamo; Valadão, Iuri Cordeiro; Modestia, Silvestre Massimo; Mattioli, Sarah Viana [UNESP]; Junior, Ricardo Rosa; Zalmas, Lykourgos-Panagiotis; Fang, Yun; Petsalaki, Evangelia; Krieger, José Eduardo (Springer Nature, 2023)
Endothelial dysfunction (ED) is critical in the development and progression of cardiovascular (CV) disorders, yet effective therapeutic targets for ED remain elusive due to limited understanding of its underlying molecular mechanisms. To address this gap, we employed a systems biology approach to identify potential targets for ED. Our study combined multi omics data integration, with siRNA screening, high content imaging and network analysis to prioritise key ED genes and identify a pro- and anti-ED network. We found 26 genes that, upon silencing, exacerbated the ED phenotypes tested, and network propagation identified a pro-ED network enriched in functions associated with inflammatory responses. Conversely, 31 genes ameliorated ED phenotypes, pointing to potential ED targets, and the respective anti-ED network was enriched in hypoxia, angiogenesis and cancer-related processes. An independent screen with 17 drugs found general agreement with the trends from our siRNA screen and further highlighted DUSP1, IL6 and CCL2 as potential candidates for targeting ED. Overall, our results demonstrate the potential of integrated system biology approaches in discovering disease-specific candidate drug targets for endothelial dysfunction.
Keywords: data integration; drug targets; endothelial dysfunction; network analysis; systems biology